Bridging the gap between chemical engineering education and industrial practice - (:unkn) unknown (TEMPUS PUBLICATIONS, 2007)
Being a student is usually followed by working in industry and the transition from one to the other may be challenging. In our research, we conduct a lengthy survey and ask chemical engineers, who have graduated from university in the past 10 years, to evaluate the education they received in respect of expectations in industry. We received 200 replies and quantitatively analysed the results. With information from the survey, we turned out, attention to our education system and the curriculum, suggesting some changes accordingly. Our goal with this work is to propose a system that prepares students for what they might encounter in industry. Also, we would like to suggest ways to give them better exposure to industrial applications, needs and most recent developments through industry-related coursework. As a result, our ultimate aim is to find ways to reconnect the tenuous ties between university and industry and to intensify the exchange between chemical and related (pharmaceutical, biotechnology, etc) industries, which, in the long ran, will result in mutual benefit for both academia and students.
Keywords: chemical engineering education; industry-university collaboration; curriculum change